High-Temperature, but Not High-Pressure, Conditions Alter Neuronal Activity - Mika Mizunuma; Naoya Takahashi; Atsushi Usami; Norio Matsuki; Yuji Ikegaya (Elsevier, 2009)
Abstract.: We describe the effect of high pressure and high temperature on neuronal activity. Increased intracranial pressure is generally a pathological sign observed in intracerebral hemorrhage, brain edema, and brain tumor, yet little is known about how the hyperbaric pressure per se affects neuronal activity. Using a pressure/temperature-changeable perfusion chamber, we carried out functional multineuron calcium imaging to record spontaneous spiking activity simultaneously from about 100 neurons in hippocampal slice cultures. High-pressure conditions (up to 100 mmHg) did not alter the network excitability, whereas high-temperature conditions (up to 40°C) increased synchronized network activity. Thus, neurons are sensitive to feverish conditions, but the acute hyperbaric circumstance itself is unlikely to exert a detrimental effect on neuronal function. Keywords:: pressure, calcium imaging, neuronal network